(untitled) (Indianapolis, IN, 1996)
Enables Visual Basic programmers to advance to the most recent level with expert techniques and strategies that explain how to exploit the newest features of Visual Basic as well as implement VBA in a network setting
Keywords: Basic ( computer program language ),Ngôn ngữ lập trình căn bản